2015
DOI: 10.1038/bjc.2015.64
|View full text |Cite
|
Sign up to set email alerts
|

IL8 polymorphisms and overall survival in pazopanib- or sunitinib-treated patients with renal cell carcinoma

Abstract: Background:We evaluated germline single nucleotide polymorphisms (SNPs) for association with overall survival (OS) in pazopanib- or sunitinib-treated patients with advanced renal cell carcinoma (aRCC).Methods:The discovery analysis tested 27 SNPs within 13 genes from a phase III pazopanib trial (N=241, study 1). Suggestive associations were then pursued in two independent datasets: a phase III trial (COMPARZ) comparing pazopanib vs sunitinib (N=729, study 2) and an observational study of sunitinib-treated pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 39 publications
0
37
0
Order By: Relevance
“…With regard to pazopanib, SNPs in UGT1A1, CYP1A2, and HFE were associated with either bilirubin levels or ALT levels, and SNPs in IL8, HIF1A, NR1I2, and VEGFA were associated with efficacy outcomes on pazopanib. The association of rs1126647 in IL8 with OS was confirmed in two independent data sets including patients treated with either sunitinib or pazopanib [40,42]. Sorafenib toxicity and efficacy were related to genetic polymorphisms in ABCC2, HLA-A, and the only large study (n > 300) available on sorafenib treatment showed rs2071559 in VEGF-R2 was related to efficacy.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…With regard to pazopanib, SNPs in UGT1A1, CYP1A2, and HFE were associated with either bilirubin levels or ALT levels, and SNPs in IL8, HIF1A, NR1I2, and VEGFA were associated with efficacy outcomes on pazopanib. The association of rs1126647 in IL8 with OS was confirmed in two independent data sets including patients treated with either sunitinib or pazopanib [40,42]. Sorafenib toxicity and efficacy were related to genetic polymorphisms in ABCC2, HLA-A, and the only large study (n > 300) available on sorafenib treatment showed rs2071559 in VEGF-R2 was related to efficacy.…”
Section: Discussionmentioning
confidence: 72%
“…However, the effects on total drug exposure resulting from changes in CYP enzyme activity may be very different for sunitinib and pazopanib. Including both sunitinib-and pazopanib-treated patients in this type of analyses is not very reasonable [41,42], since sunitinib is converted to an active metabolite with similar activity and potency and a longer half-life, while pazopanib only has less active metabolites. In addition, the extent of absorption for pazopanib and sunitinib may be very different (due to substrate specificity, for example), and its role in the total PK of the TKI is unclear.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations